Das Institut. (1st August 2013) - Shaw, Hannah
"Nichts, Nichts!", recently on view at the Kölnischer Kunstverein, invited visitors to step inside a glamorous, though somewhat seedy department store. Born in Germany but now based in New York City, artists Kerstin Brätsch and Adele Röder have collaborated under the banner of DAS INSTITUT since 2007, which they describe as an import/export agency. Readily visible from the street, "Nothing, Nothing!" was split into two sections or identities: the first was a deliberate, over-the- top exercise in self-branding, while the second offered a more sublimated, Godardian perspective. The ground floor space was decorated with brightly colored sheets of Plexiglas and assorted works of art. A stack of paintings rested against a wall, some were hung from a rack, and others attached by magnets to their frames as if ready to be taken home on the spot.